Posttranslational modifications of blood-derived alpha-synuclein as biochemical markers for Parkinson's disease - Miranda, Hugo Vicente (2017)
We are thankful to the patients and participants for their kind participation and donation of samples. This study was supported by Fundacao para a Ciencia e Tecnologia (FCT) EXPL/NEU-OSD/0606/2012, PTDC/NEUOSD/5644/2014. Authors were supported by: HVM (FCT, SFRH/BPD/64702/2009, SFRH/BPD/109347/2015); MG (FCT, EXPL/NEU-OSD/0606/2012); TFO (DFG Center for Nanoscale Microscopy and Molecular Physiology of the Brain-CNMPB).